Interacciones medicamentosas en pacientes con enfermedad de Parkinson en un programa de atención domiciliaria - Poggi, Estefania (2023)
Objective: to identify the drug interactions present in the prescriptions filled by patients with Parkinson’s disease from the service of the home care program. Methodology: An observational, descriptive, retrospective cross-sectional study was designed. Results: The review of 548 filled prescriptions was carried out, 439 (80.1%) presented drug interactions, where the male sex and the age group of ≥ 80 years predominated and the most frequent comorbidities were arterial hypertension, chronic gastritis and heart failure. From the review of 439 filled prescriptions, 943 drug interactions were found. Carbidopa/Levodopa presented a higher number of drug interactions. The predominant drug interaction mechanism was pharmacodynamic (413) and according to the evaluation of the prescriptions filled through Drugs.com and classified under the Stockley Alerts criteria, 764 (81.0%) were found to be moderate and 179 (19.0% ) as high. Conclusion: There are drug interactions in the prescriptions filled by patients with Parkinson’s disease from the home care program service, therefore, the need for the intervention of the Pharmaceutical Chemist professional in the pharmacotherapy and pharmacovigilance of patients to prevent the incidence of drug interactions.